Method for detecting collusion attack node in road condition information sharing based on reputation point - Shichang XUAN; Hao TANG; Wu YANG (Tongxin xuebao)
Aiming at the problem that on occasion of the release of false road condition information by collusion nodes in the Internet of vehicles collaboratively, message authenticity could not be guaranteed in the process of road condition information sharing, a method for detecting collusion attack nodes in road condition information sharing based on reputation points was proposed.In the process of road condition information aggregation, a malicious information detection algorithm was designed to detect false messages issued by colluding nodes, which could ensure the authenticity and accuracy of messages delivered in the system.Experimental results show that the proposed method has higher detection efficiency for collusion nodes and adaption to a proportion of collusion nodes through security evaluation and experiments in comparison with the existing schemes.